DESIGN AND IMPLEMENTATION OF HARDWARE ON MOVEMENT CONVERSION, POWER SUPPLY, AND SENSOR IN STORAGE AND RETRIEVAL RACKING SYSTEM OF WAREHOUSES - Siddiq, Jakfar
Automatic warehousing has been widely applied in industries with benefits in the form of increased work operation efficiency, security, and accuracy in storing goods. Has designed and implemented a system of storage and retrieving goods on racks in industrial warehouses with a prototype method. In this final project book focuses on the design and implementation of movement conversion, power supply, and system detection. The design of the movement conversion is carried out to determine the shape of the resulting movement on the conversion of mileage, speed and carrying capacity. The shape of the movement was also observed using the jacobian matrix and inverse kinematic methods. The results obtained are that the plant system can be designed with a horizontal movement speed of 23.76 cm / s, a vertical upward movement of 6.93 cm / s, a vertical downward movement of 2.58 cm / s, and a carrier fork movement of 10 , 92 cm / s. On power supply implementation are able to provide a voltage value of 12.11 V at the output port. The detection in the form of an encoder shows the result that there is an excess recording count which affects the system distance that passes the target of 0.59 cm (horizontal motor) and 0.1 cm (vertical motor) with a PWM value of 150.